A rational formula to predict punching shear capacity at interior columns connections with RC flat slabs reinforced with either steel or FRP bars but without shear reinforcement. (March 2022) - Alrudaini, Thaer M. Saeed
Abstract: In this study, a new rational but simple and one accurate equation is proposed to estimate the punching shear capacity of concrete flat slabs reinforced by either steel or FRP bars but without shear reinforcement instead of different equations for the two different reinforcement materials. The proposed model is verified based on extensive experimental tests presented in the literature in which the accuracy of the developed equation is investigated. In addition, the predictions using the proposed equation are compared with those obtained by using specified equations by several design codes and standards as well as those obtained by adopting other models proposed by other researchers. Comparison results showed that the proposed model provides the most accurate predictions with less scatters compared with the other available models. For the steel reinforced concrete flat slabs, the proposed equation provides results with mean value of the measured to estimated punching shear capacity ratio equal to 1.00 ± 0.09 with coefficient of variations of 9.33%. On the other hand, for FRP reinforced concrete flat slabs, the proposed model shows mean value of the measured to estimated punching shear capacity ratio equal to 1.13 ± 0.16 with coefficient of variations of 14.28%.